What is Iconella (Bacillariophyta)? The poverty of molecular monophyly (Part II) - Williams, David M. (Phytotaxa, 2024)
In 2020 I gave a talk to my colleagues in the Natural History Museum, London with the title ‘Taxonomy: Who are these Performing Monkeys?’ The title is derived from a paper by Arthur Cain (1921-1999), ecologist, evolutionary biologist and malacologist, published in 1959 but presented a year earlier, on the 15th July 1958, at the Royal Geographical Society to commemorate the bi-centenary of Linnaeus’s Systema Naturae: ‘Is it not extraordinary that young taxonomists are trained like performing monkeys, almost wholly by imitation, and that in only the rarest cases are they given any instruction in taxonomic theory?’ (Cain 1959, p. 243). Cain concluded his presentation with the following remarks: